Die geschlechtsspezifische Lohnlücke - Hirsch, Boris (Wirtschaftsdienst, 2010)
WiSo-Import:2015-03-26:482
Keywords: Transformation

Differences in Labor Supply to Monopsonistic Firms and the Gender Pay Gap: An Empirical Analysis Using Linked Employer-Employee Data from Germany - Hirsch, Boris; Schank, Thorsten; Schnabel, Claus (Journal of Labor Economics, 2010)

Do Better Pre-Migration Skills Accelerate Immigrants' Wage Assimilation? - Hirsch, Boris; Jahn, Elke; Toomet, Ott; Hochfellner, Daniela (Labour Economics, 2014)

Do Women Benefit from Competitive Markets? Product Market Competition and the Gender Pay Gap in Germany - Hirsch, Boris; Oberfichtner, Michael; Schnabel, Claus (Economics Bulletin, 2012)
Using a large linked employer–employee dataset for Germany with a direct plant-level measure of product market competition and controlling for job-cell fixed effects, we investigate whether relative wages of women benefit from strong competition. We find that the unexplained gender pay gap is about 2.4 log points lower in West German plants that face strong product market competition than in those experiencing weak competition, whereas no such link shows up for East Germany. <br
Keywords: Gender Pay Gap; Discrimination; Product Market Competition; Germany

Dual Labor Markets at Work: The Impact of Employers' Use of Temporary Agency Work on Regular Workers' Job Stability - Hirsch, Boris (Industrial & Labor Relations Review, 2016)
Fitting duration models on an inflow sample of jobs in Germany starting in 2002 to 2010, the author investigates the impact of employers’ use of temporary agency work on regular workers’ job stability. In line with dual labor market theory, the author finds that nontemporary jobs are significantly more stable when employers use temporary agency workers. The rise in job stability stems mainly from reduced transitions into nonemployment, suggesting that nontemporary workers are safeguarded against involuntary job losses. The findings are robust to controlling for unobserved permanent employer characteristics and changes in the observational window that comprises the labor market disruption of the Great Recessio
Keywords: temporary agency work; temporary workers; job stability; job security; dual labor markets; duration analysis; labor market flexibility

Firm Leadership and the Gender Pay Gap: Do Active Owners Discriminate more than Hired Managers? - Hirsch, Boris; Müller, Steffen (Journal for labour market research, 2014)
WiSo-Import:2015-03-26:4567

Geschlechterlohnlücke: gerechtfertigt oder diskriminierend? - Hirsch, Boris; Schnabel, Claus (Personal quarterly, 2013)
WiSo-Import:2015-03-26:4097
Keywords: Geschlechterlohnlücke; Diskriminierung

How Selective Are Real Wage Cuts? A Micro-Analysis Using Linked Employer-Employee Data - Hirsch, Boris; Zwick, Thomas (Labour, 2015)
Using linked employer–employee panel data for Germany, we investigate whether firms implement real wage reductions in a selective manner. In line with insider–outsider and several strands of efficiency wage theory, we find strong evidence for selective wage cuts with high‐productivity workers being spared even when controlling for permanent differences in firms' wage policies. In contrast to some recent contributions stressing fairness considerations, we also find that wage cuts increase wage dispersion among peers rather than narrowing it. Notably, the same selectivity pattern shows up when restricting our analysis to firms covered by collective agreements or having a works counci

Is There a Gap in the Gap? Regional Differences in the Gender Pay Gap - Hirsch, Boris; König, Marion; Möller, Joachim (Scottish Journal of Political Economy, 2013)

Is There Monopsonistic Discrimination Against Immigrants? - Hirsch, Boris; Jahn, Elke (Industrial & Labor Relations Review, 2015)

Is there monopsonistic discrimination against immigrants? First evidence from linked employer-employee data - Hirsch, Boris; Jahn, Elke (2012)
This paper investigates immigrants’ and natives’ labour supply to the firm within a semi-structural approach based on a dynamic monopsony framework. Applying duration models to a large administrative employer–employee data set for Germany, we find that once accounting for unobserved worker heterogeneity immi-grants supply labour less elastically to firms than natives. Under monopsonistic wage setting the estimated elasticity differential predicts a 4.7 log points wage penalty for immigrants thereby accounting for almost the entire unexplained native–immigrant wage differential of 2.9–5.9 log points. Our results imply that employers profit from discriminating against immigrant
WiSo-Import:2015-08-12:4721

Monopsonistic Labour Markets and the Gender Pay Gap: Theory and Empirical Evidence - Hirsch, Boris (Springer, 2010)
This book investigates models of spatial and dynamic monopsony and their application to the persistent empirical regularity of the gender pay gap. Theoretically, the main conclusion is that employers possess more monopsony power over their female employees if women are less driven by pecuniary considerations in their choice of employers than men. Employers may exploit this to increase their profits at the detriment of women's wages. Empirically, it is indeed found that women's labour supply to the firm is less wage-elastic than men's and that at least a third of the gender pay gap in the data investigated may result from employers engaging in monopsonistic discrimination. Therefore, a monopsonistic approach to gender discrimination in the labour market clearly contributes to the economic understanding of the gender pay gap. It not only provides an intuitively appealing explanation of the gap from standard economic reasoning, but it is also corroborated by empirical observatio
WiSo-Import:2015-04-13:481
Keywords: Transformation; Forschungsbericht 2010

Regionale Unterschiede im 'Gender Pay Gap': Lohnabstand von Frauen in der Stadt kleiner als auf dem Land - Hirsch, Boris; König, Marion; Möller, Joachim (2009)

The Effect of Housework on Wages in Germany: No Impact at All - Hirsch, Boris; Konietzko, Thorsten (Journal for labour market research, 2013)

The Gender Pay Gap Under Duopsony: Joan Robinson Meets Harold Hotelling - Hirsch, Boris (Scottish Journal of Political Economy, 2009)
This paper presents an alternative explanation of the gender pay gap resting on a simple Hotelling-style duopsony model of the labour market. Since there are only two employers, equally productive women and men have to commute and face travel cost to do so. We assume that some women have higher travel cost, e.g., due to more domestic responsibilities. Employers exploit that women on average are less inclined to commute and offer lower wages to all women. Since women's firmlevel labour supply is for this reason less wage-elastic, this model is in line with Robinson's explanation of wage discrimination. © 2009 The Author Journal compilation © 2009 Scottish Economic Society. Published by Blackwell Publishing Lt
WiSo-Import:2015-03-26:4098

The Impact of Female Managers on the Gender Pay Gap: Evidence from Linked Employer-Employee Data for Germany - Hirsch, Boris (Economics letters, 2013)

The Levelling Effect of Product Market Competition on Gender Wage Discrimination - Hirsch, Boris; Oberfichtner, Michael; Schnabel, Claus (IZA Journal of Labor Economics, 2014)
Using linked employer-employee panel data for West Germany that include direct information on the competition faced by plants, we investigate the effect of product market competition on the gender pay gap. Controlling for match fixed effects we find that intensified competition significantly lowers the unexplained gap in plants with neither collective agreements nor a works council. Conversely, there is no effect in plants with these types of worker codetermination, which are unlikely to have enough discretion to adjust wages in the short run. We also document a larger competition effect in plants with few females in their workforces. Our findings are in line with Beckerian taste-based employer wage discrimination that is limited by competitive forces.
Keywords: discrimination; product marcet competition; gender pay gap

The Productivity Effect of Temporary Agency Work: Evidence from German Panel Data - Hirsch, Boris; Müller, Steffen (Economic Journal, 2012)
This study investigates the effect of temporary agency work on the user firm’s productivity. We hypothesise that using temporary agency work to enhance numerical flexibility and to screen job candidates may increase productivity, whereas temporary workers’ lower firm‐specific human capital and spillover effects on the user’s permanent employees may adversely affect productivity. Other than the sparse existing literature on this issue, we exploit a large panel data set and control for time‐invariant and time‐varying unobserved heterogeneity by using the system GMM estimator. We find a robust hump‐shaped effect of the extent of temporary agency work on the user firm’s productivit
WiSo-Import:2015-03-26:4099

What Can We Learn from Bargaining Models about Union Power? The Decline in Union Power in Germany, 1992-2009 - Hirsch, Boris; Schnabel, Claus (Manchester School, 2014)
Building on the right-to-manage model of collective bargaining, this paper tries to infer union power from the observed results in wage setting. It derives a time-varying indicator of union strength taking account of taxation, unemployment benefits, and the labour market situation and confronts this indicator with annual data for Germany. The results show that union power did not change much from 1992 to 2002 but fell markedly (by about one-third) from 2002 to 2007 in the aftermath of substantial labour market reform

Women Move Differently: Job Separations and Gender - Hirsch, Boris; Schnabel, Claus (Journal of Labor Research, 2012)
Using a large German linked employer-employee data set and methods of competing risks analysis, this paper investigates gender differences in job separation rates to employment and nonemployment. In line with descriptive evidence, we find lower job-to-job and higher job-to-nonemployment transition probabilities for women than men when controlling for individual and workplace characteristics and unobserved plant heterogeneity. These differences vanish once we allow these characteristics to affect separations differently by gender. When additionally controlling for wages, we find that both separation rates are considerably lower and also significantly less wage-elastic for women than for me

Works Councils and Separations: Voice, Monopoly, and Insurance Effects - Hirsch, Boris; Schank, Thorsten; Schnabel, Claus (Industrial relations, 2010)
Using a large linked employer–employee data set for Germany, we find that the existence of a works council is associated with a lower separation rate to employment, in particular for workers with low tenure. While works council monopoly effects show up in all specifications, clear voice effects are only visible for low tenured workers. Works councils also reduce separations to nonemployment, and this impact is more pronounced for men. Insurance effects only show up for workers with tenure of more than 2 years. Our results indicate that works councils to some extent represent the interests of a specific clientele.